Key to Nine Common Smilax Species of Florida - Lynn Proenza; Michael Andreu (EDIS)
Identifying species found in Smilax the genus can be difficult because species resemble one another closely. One must be careful to use detailed descriptions in order to correctly identify a specimen. Smilax species are important because they can provide shelter and food for wildlife and have provided humans with medicine, food, and dyes. Twelve Smilax species are found in Florida. This 8-page fact sheet covers the nine more common species that one may encounter in the state. Written by Lynn Proenza and Michael Andreu and published by the UF Department of School of Forest Resources and Conservation, January 2013.